2020
DOI: 10.1093/ofid/ofaa176
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Etiology of Pyogenic Vertebral Osteomyelitis According to Patient Characteristics

Abstract: Background It is difficult to select an appropriate empirical antibiotic treatment regimen for patients with culture-negative pyogenic vertebral osteomyelitis (PVO). Having knowledge of the distribution of microorganisms according to patient characteristics can help clinicians make informed choices regarding empirical antibiotics. The aim of this study was to determine the microbial distribution among individuals with PVO according to their demographic and clinical characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
3
21
2
1
Order By: Relevance
“…In accordance with other studies, the majority of our PVO population was found to consist of elderly men presenting with back pain and elevated CRP (Chang et al, 2018;Chong et al, 2018;Jeon et al, 2020;Kim et al, 2020;Vettivel et al, 2019). These findings were consistent with a previous study from our institution by Aagaard et al, using a similar design, on 100 PVO patients admitted from 2006 to 2011 (Aagaard et al, 2013).…”
Section: Comparison With the Literaturesupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with other studies, the majority of our PVO population was found to consist of elderly men presenting with back pain and elevated CRP (Chang et al, 2018;Chong et al, 2018;Jeon et al, 2020;Kim et al, 2020;Vettivel et al, 2019). These findings were consistent with a previous study from our institution by Aagaard et al, using a similar design, on 100 PVO patients admitted from 2006 to 2011 (Aagaard et al, 2013).…”
Section: Comparison With the Literaturesupporting
confidence: 93%
“…In general, our study reported similar demographics and comorbidities to those in previous reports (Chong et al, 2018;Jeon et al, 2020;Kim et al, 2020;Lee et al, 2019).…”
Section: Comparison With the Literaturesupporting
confidence: 87%
See 1 more Smart Citation
“…Diabetes is the most common underlying disease, although there are reports that pyogenic spondylitis caused by Gram-negative bacteria is related to diabetes [15]. However, our study and Dong Youn Kim et al [16] did not nd any connection between these two factors.…”
Section: Discussioncontrasting
confidence: 77%
“…This finding is similar to that reported by a previous domestic study in which MRSA was identified as the causative agent in 44% of the overall cases of S. aureus osteoarticular infections [ 3 ]. MRSA has also been reported to be the causative agent in 38 - 43% cases of native vertebral osteomyelitis in Korea [ 4 5 ]. Lee et al showed that a high MRSA ratio was associated with high resistance rates to ciprofloxacin (34.3%) and clindamycin (42.9%) in cases of S. aureus infection [ 2 ].…”
mentioning
confidence: 99%